Vitamin C protected in concentrate of Cavia porcellus "cuy" in growth-fattening stage, excluding forage - León, Zara (2016)
The aim of this study was to determine how vitamin C affects protected concentrate Cavia porcellus "cuy" except forage on performance in growth stage - fattening. Materials and methods. 120 improved and weaned (14 days +/- 3 days) male cuy, genotype were randomly distributed in 4 treatments with 30 repetitions: T0: Concentrate + water + forage, T1: 45 mg of Vitamin C / 100 g of concentrate + water, T2: 55 mg of Vitamin C / 100 g of water and concentrated + T3: 66 mg of Vitamin C / 100 g concentrate + water. They were evaluated: final weight increase (IPF), daily weight increase (IPD), feed conversion (CA) and benefit / cost (B/C). Data were analyzed with the test of homogeneity of variance Levenne, ANOVA and Duncan test were used. Results and conclusions. Significant differences (p < 0.05) for IPF between T1 treatment (632.93 g) for T2, T3 and T0 and CA IPD and no significant differences (p > 0.05) between treatments. The best ratio B/C was obtained in T1 (1.48). It is concluded that vitamin C at 45 mg / 100 g of concentrate + water had the best effect on the increase in final weight and the best benefit - cost in C. porcellus in the growth stage - fattening, constituting a viable alternative.